Regulation of fatty acid degradation in Escherichia coli: isolation and characterization of strains bearing insertion and temperature-sensitive mutations in gene fadR. - Simons, R W (1980)
Transposon Tn10 was used to mutagenize the fadR gene in Escherichia coli. Mutants bearing fadR:Tn10 insertion mutations were found to (i) utilize the noninducing fatty acid decanoate as sole carbon source, (ii) beta-oxidize fatty acids at constitutive rates, and (iii) contain constitutive levels of the five key beta-oxidative enzymes. These characteristics were identical to those observed in spontaneous fadR mutants. The constitutive phenotype presented by the fadR:Tn10 mutants was shown to be genetically linked to the associated transposon-encoded drug resistance. These results suggest that the fadR gene product exerts negative control over the fatty acid degradative regulon. The fadR gene of E. coli has been mapped through the use of transposon-mediated fadR insertion mutations. The fadR locus is at 25.5 min on the revised map and cotransduces with purB, hemA, and trp. Three-factor conjugational and transductional crosses indicate that the order of loci in this region of the chromosome is purB-fadR-hemA-trp. Spontaneous fadR mutants were found to map at the same location. Strains that exhibit alterations in the control of the fad regulon in response to changes in temperature were also isolated and characterized. These fadR(Ts) mutants were constitutive for the fad enzymes at elevated temperatures and inducible for these activities at low temperatures. The fadR(Ts) mutations also map at the fadR locus. These results strongly suggest that the fadR gene product is a repressor protein.